Efektivitas Google Class Room Terhadap Kinerja Guru di Sekolah Menengah Kejuruan - Umi Mahdhuroh; Hindarto Hindarto; Jasno Jasno; Rulli Widiantoro; Budi Murtiyasa (TIN: Terapan Informatika Nusantara, 2026)
In the field of education, speed has become a vital factor in achieving objectives, including the improvement of teacher performance. Digital transformation in education has driven the adoption of various technologies, one of which is Google Classroom. In Vocational High Schools (SMK), which are oriented toward competency and job readiness, the integration of technology in learning has become an absolute necessity.This research aims to:1) Analyze the effectiveness of implementing a Learning Management System (LMS) in improving the performance of SMK teachers.2) Identify the obstacles faced by administrators and teachers in implementing Google Classroom. This study employs a Mixed Methods approach (quantitative and qualitative) with a descriptive design. Data collection was conducted using three methods: interviews, observations, and documentation (documents or texts). The results of this study found that the application of Google Classroom, when implemented optimally, can significantly improve administrative efficiency, the quality of lesson planning and execution, collaboration, and the teacher's ability to conduct assessments and evaluations. The primary challenges lie in infrastructure readiness, training, and a shift in mindset. The research concludes that Google Classroom is not merely a supporting tool but a catalyst for enhancing teacher professionalism in the digital era. It reveals that the comprehensive and optimal implementation of Google Classroom contributes significantly to improved teacher performance. Concrete benefits identified include: Increased administrative efficiency and material management. Enhanced quality of instructional planning and interaction. Easier collaboration among teachers and with students.Strengthened capabilities in diverse and data-driven assessments and evaluations. However, behind this potential, the study also identified several key challenges. These challenges are not only technical, such as infrastructure and network limitations, but also encompass human resource aspects, such as the need for continuous training and, most crucially, a change in mindset shifting from conventional methods toward a digital learning paradigm that is more collaborative and flexible.